FOXO1 Mediates Advanced Glycation End Products Induced Mouse Osteocyte-Like MLO-Y4 Cell Apoptosis and Dysfunctions - Citong Zhang; Wei Wei; Minghan Chi; Yao Wan; Xue Li; Manlin Qi; Yanmin Zhou (Journal of Diabetes Research)
Osteocyte plays an essential role in bone metabolism by regulating osteoblast and osteoclast activities. Dysfunction or apoptosis of osteocyte will severely endanger the bone homeostasis and result in bone diseases such as osteoporosis. Osteoporosis has been considered as one of the diabetes complications; however, the mechanism is still to be discovered. Advanced glycation end products (AGEs), as the main pathogenic factor of diabetes mellitus, have the capacity to induce osteocyte apoptosis thus sabotaging bone homeostasis. Here, we examined the role of AGE during osteocyte apoptosis and how this effect would affect osteocyte’s regulation of osteoblast and osteoclast. Mouse osteocyte-like MLO-Y4 cells were used to study the properties of osteocyte and to examine its biological and pathological function. MTT assay and Annexin V assay showed that AGE significantly induce MLO-Y4 cell apoptosis. qPCR and Western blot results have shown that AGE upregulates proapoptotic gene p53 and its downstream target gene Bax, which leads to enhanced activation of caspase-3, thus inducing apoptosis in MLO-Y4 cells. Increased expression of sclerostin and RANKL in osteocytes has shown that AGE induces osteocyte dysfunction thus severely damaging the bone homeostasis by decreasing osteoblast and increasing osteoclast activities. Furthermore, the role of the transcription factor FOXO1, which is intensely associated with apoptosis, has been determined. Western blot has shown that AGE significantly decreases Akt activities. Immunofluorescence has shown that AGE promotes FOXO1 nuclei localization and enhances FOXO1 expression. Silencing of FOXO1 suppressed AGE-enhanced apoptosis; mRNA and protein expressions of cleaved caspase-3, sclerostin, and RANKL were downregulated as well. Moreover, exogenous FOXO1 increased caspase-3 mRNA levels and caspase-3 transcriptional activity. Lastly, ChIP assay has established the capacity of FOXO1 binding directly on the caspase-3, sclerostin, and RANKL promoter region in AGE environment, providing the mechanism of the AGE-induced osteocyte apoptosis and dysfunction. Our results have shown that FOXO1 plays a crucial role in AGE-induced osteocyte dysfunction and apoptosis through its regulation of caspase-3, sclerostin, and RANKL. This study provides new insight into diabetes-enhanced risk of osteoporosis given the critical role of AGE in the pathogenesis of diabetes and the essential part of osteocyte in bone metabolism.